2024
DOI: 10.3847/1538-4357/ad07d0
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Faint Resolved Galaxies Beyond the Milky Way in DES Year 6: A New Faint, Diffuse Dwarf Satellite of NGC 55

M. McNanna,
K. Bechtol,
S. Mau
et al.

Abstract: We report results from a systematic wide-area search for faint dwarf galaxies at heliocentric distances from 0.3 to 2 Mpc using the full 6 yr of data from the Dark Energy Survey (DES). Unlike previous searches over the DES data, this search specifically targeted a field population of faint galaxies located beyond the Milky Way virial radius. We derive our detection efficiency for faint, resolved dwarf galaxies in the Local Volume with a set of synthetic galaxies and expect our search to be complete to M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 183 publications
0
2
0
Order By: Relevance
“…Recent observational programs have revealed the spatial clustering of dwarf galaxies in the vicinity of LMC (e.g., Bechtol et al 2015;Drlica-Wagner et al 2015;Koposov et al 2015). There is a significant ongoing effort to map out the halos of several low-mass galaxies and search for their satellite populations, e.g., PandAS around M33 (with CFHT/MegaCam, two possible satellites have been reported; Martin et al 2009Martin et al , 2013aMartínez-Delgado et al 2022), the MADCASH Survey (a DECam+ Hyper Suprime-Cam (HSC) deep-imaging campaign around a dozen isolated nearby low-mass galaxies, where three satellites have been reported: one around NGC 2403, one around NGC 4214, and one around NGC 3109; Sand et al 2015;Carlin et al 2016Carlin et al , 2021, and DELVE-DEEP (with DECam, one satellite has been reported around NGC 55; McNanna et al 2024). Therefore, it is not surprising to observe a similar clustering of dwarf galaxies in the vicinity of NGC 247.…”
Section: Galex Uv Imagingmentioning
confidence: 99%
“…Recent observational programs have revealed the spatial clustering of dwarf galaxies in the vicinity of LMC (e.g., Bechtol et al 2015;Drlica-Wagner et al 2015;Koposov et al 2015). There is a significant ongoing effort to map out the halos of several low-mass galaxies and search for their satellite populations, e.g., PandAS around M33 (with CFHT/MegaCam, two possible satellites have been reported; Martin et al 2009Martin et al , 2013aMartínez-Delgado et al 2022), the MADCASH Survey (a DECam+ Hyper Suprime-Cam (HSC) deep-imaging campaign around a dozen isolated nearby low-mass galaxies, where three satellites have been reported: one around NGC 2403, one around NGC 4214, and one around NGC 3109; Sand et al 2015;Carlin et al 2016Carlin et al , 2021, and DELVE-DEEP (with DECam, one satellite has been reported around NGC 55; McNanna et al 2024). Therefore, it is not surprising to observe a similar clustering of dwarf galaxies in the vicinity of NGC 247.…”
Section: Galex Uv Imagingmentioning
confidence: 99%
“…far only been circumstantial (e.g., Belokurov et al 2006;Torrealba et al 2019;Collins et al 2020;Ji et al 2021). The situation is also not clear for NGC 55-dw1, which, in addition to lacking clear tidal features, does not yet have a directly measured distance (McNanna et al 2024). Among the NGC 253 satellites, MM-dw2 is most similar to SNFC-dw1, and it exhibits a highly elongated shape (see Figure 1).…”
Section: Discussion and Summarymentioning
confidence: 98%